Facile preparation of polysaccharide-based sponges and their potential application in wound dressing. Issue 4 (10th January 2018) - Cheng, Huan; Li, Chaojing; Jiang, Yujia; Wang, Bijia; Wang, Fujun; Mao, Zhiping; Xu, Hong; Wang, Lu; Sui, Xiaofeng
Abstract : A cellulose–chitosan hybrid sponge incorporating sustainability, desired functionality and stability was used as a wound dressing. Abstract : Wound exudate adsorption and blood clotting are of critical importance for promoting wound healing in diabetic patients. In this study, cellulose–chitosan hybrid sponges were prepared by a facile pathway with controllable structure and morphology. Aimed at wound dressing, the physical properties, cytocompatibility, and hemocompatibility of the cellulose–chitosan hybrid sponges were evaluated. The results indicated that the hybrid sponges were non-toxic and outperformed silicon in promoting blood coagulation. The sponges could also effectively adsorb abundant wound exudate due to their highly porous structure. Moreover, the maximal shape recovery of these chemically crosslinked sponges from a 50% compression strain was up to 95% of their original thickness, without obviously compromising their macro/microstructure and mechanical properties after 10 cycles. The superior blood coagulation, adsorption performance, and shape recovery properties of the sponges make them ideal for use in making wound dressings for diabetic patients.